SOX10 regulates multiple genes to direct eumelanin versus pheomelanin production in domestic rock pigeon. (21st March 2019) - Domyan, Eric T.; Hardy, Jeremy; Wright, Tanner; Frazer, Cody; Daniels, Jordan; Kirkpatrick, Joshua; Kirkpatrick, Jacob; Wakamatsu, Kazumasa; Hill, Jonathon T.
Abstract: The domesticated rock pigeon ( Columba livia ) has been bred for hundreds of years to display an immense variety of ornamental attributes such as feather color and color patterns. Color is influenced by multiple loci that impact the type and amount of melanin deposited on the feathers. Pigeons homozygous for the "recessive red" mutation, which causes downregulation of Sox10, display brilliant red feathers instead of blue/black feathers. Sox10 encodes a transcription factor important for melanocyte differentiation and function, but the genes that mediate its promotion of black versus red pigment are unknown. Here, we present a transcriptomic comparison of regenerating feathers from wild‐type and recessive red pigeons to identify candidate SOX10 targets. Our results identify both known and novel targets, including many genes not previously implicated in pigmentation. These data highlight the value of using novel, emerging model organisms to gain insight into the genetic basis of pigment variation.